Fábula PXP - a técnica de Programação Exploratória (PXP): projetos de criação e desenvolvimento de jogos digitais - Lemes, David de Oliveira (2015)
The development of digital games is an activity that grows exponentially as the many game supporting devices become popular. Under the game development perspective, nowadays, several tools "promise" to make the most inexperienced programmer able to create and develop a digital game. This research presents a work model that seeks to introduce the importance of narrative into games, the way the ideas are organized to produce a digital game and, overall, a programming technique that will help the game designer, or digital games designer to understand how a calculations, the computer, may enhance or hinder the use of ideas and original narrative of a project